2019
DOI: 10.5688/ajpe6809
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Whether Transfer of Learning in Pharmacy Students Depends More on Knowledge Storage or Accessibility

Abstract: Objective. To investigate whether prior knowledge or reactivated marginal knowledge alone is sufficient for student pharmacists to transfer foundational science content to pharmacy application. Methods. In two experiments, transfer of foundational science knowledge was examined. Far transfer was examined by investigating the relationship between prior knowledge of chemistry and physiology to pharmacokinetic application. Near transfer was examined by investigating the relationship between foundational physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Thus, it is likely that practical knowledge learnt in pharmacies helped the third-year students to succeed in this case better, as learning in practice fosters the integration of theoretical knowledge to practice and deepens the theoretical understanding of pharmaceutical knowledge (Katajavuori et al, 2006 ). Research has shown that applying basic knowledge in practical problem-solving situations poses challenges for learners, and therefore learning activities and assignments supporting this, such as case tasks, are important particularly in the early phases of studying (e.g., Boshuizen et al, 2020 ; Persky & Murphy, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that practical knowledge learnt in pharmacies helped the third-year students to succeed in this case better, as learning in practice fosters the integration of theoretical knowledge to practice and deepens the theoretical understanding of pharmaceutical knowledge (Katajavuori et al, 2006 ). Research has shown that applying basic knowledge in practical problem-solving situations poses challenges for learners, and therefore learning activities and assignments supporting this, such as case tasks, are important particularly in the early phases of studying (e.g., Boshuizen et al, 2020 ; Persky & Murphy, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that students typically struggle in applying basic knowledge in practical problem-solving situations, such as solving case tasks (e.g. Boshuizen et al, 2020 ), also in pharmacy context (Persky & Murphy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge must be captured and stored in the organizations' repositories, such as databases, records, and software. Knowledge Retention is a fundamental part of learning and development within an organization as it allows knowledge to be used effectively and efficiently (Persky & Murphy, 2019). Knowledge retention plays a significant role in knowledge management, allowing organizations to store, access, and use the knowledge and information necessary to make decisions and inform their operations (Hislop et al, 2018).…”
Section: Background Of the Studymentioning
confidence: 99%